PEMBERDAYAAN UMKM LOKAL DAN PELESTARIAN BUDAYA TRADISIONAL MELALUI DIGITAL MARKETING KELURAHAN RANDUSARI, KOTA PASURUAN - Yufenti Oktafiah,; Nurul Akramiah,; Sri Hastari, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
Empowering UMKM not only contributes to the development of the individual or business, but also has a positive impact on the local economy. The aim of this Community Service is to empower local UMKM through digital marketing training. The method used in this article is a qualitative method with literature study or Library Research. To increase competitive advantage, UMKM need to increase adaptation to developments in marketing technology that are currently developing, such as capabilities in social media or digital marketing. Marketing training for local UMKM through digital marketing development to encourage the community's economy to improve and keep up with current developments. . It is necessary to utilize digital platforms as global media so that they can reach a wider audience, especially the millennial generation. Currently, the growth of digital media is so fast and easy, providing equal access opportunities for everyone in all parts of the world. With the mentoring and training program, the training participants gain new knowledge and understanding regarding digital platforms which can be used as a medium to promote their products